From PERK to RIPK1: Design, synthesis and evaluation of novel potent and selective necroptosis inhibitors - Scarpellini, Camilla; Valembois, Sophie; Goossens, Kenneth; Vadi, Mike; Lanthier, Caroline; Klejborowska, Greta; Van Der Veken, Pieter; De Winter, Hans; Bertrand, Mathieu J. M.; Augustyns, Koen (Frontiers in Chemistry, 2023)
Receptor-Interacting serine/threonine-Protein Kinase 1 (RIPK1) emerged as an important driver of inflammation and, consequently, inflammatory pathologies. The enzymatic activity of RIPK1 is known to indirectly promote inflammation by triggering cell death, in the form of apoptosis, necroptosis and pyroptosis. Small molecule Receptor-Interacting serine/threonine-Protein Kinase 1 inhibitors have therefore recently entered clinical trials for the treatment of a subset of inflammatory pathologies. We previously identified GSK2656157 (GSK’157), a supposedly specific inhibitor of protein kinase R (PKR)-like ER kinase (PERK), as a much more potent type II Receptor-Interacting serine/threonine-Protein Kinase 1 inhibitor. We now performed further structural optimisation on the GSK’157 scaffold in order to develop a novel class of more selective Receptor-Interacting serine/threonine-Protein Kinase 1 inhibitors. Based on a structure-activity relationship (SAR) reported in the literature, we anticipated that introducing a substituent on the para-position of the pyridinyl ring would decrease the interaction with PERK. Herein, we report a series of novel GSK’157 analogues with different para-substituents with increased selectivity for Receptor-Interacting serine/threonine-Protein Kinase 1. The optimisation led to UAMC-3861 as the best compound of this series in terms of activity and selectivity for Receptor-Interacting serine/threonine-Protein Kinase 1 over PERK. The most selective compounds were screened in vitro for their ability to inhibit RIPK1-dependent apoptosis and necroptosis. With this work, we successfully synthesised a novel series of potent and selective type II Receptor-Interacting serine/threonine-Protein Kinase 1 inhibitors based on the GSK’157 scaffold.